PERAN SUMBER DAYA MANUSIA DALAM MIGRASI PROGRAM ANALOG KE DIGITAL PADA LPP TVRI KALTENG - Satria Firdaus (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The background of this research was the emergence of International television union policy related to world television migration system from Analog to Digital. It affected to Indonesia which finally released national policy to run the Migration. The purpose of this study was to describe the role of human resource in analog to Digital Migration for Television Media In Lpp Tvri Kalteng.The research method used was qualitative descriptive with the theories of Perspective, Management, and Communication. The Result of this Research shown that the Role of Human Resource In analog to Digital Migration Program In Television Media In Lpp Tvri Kalteng is very important in the beginning and the end of program operation and its maintenance. In addition, the application of digital program have eased the supervision because in a digital system based on computerized system is very easy and simplifies broadcasting operations by realizing the quality of television especially in LPP Tvri Kalteng.The implication of this research was as a reference to the world of television in particular Human resources in migration of Analog to Digital technology so that the findings presented in this research could be an input improvement in the process of Digitalization television. Keywords : Human Resource, Analog, Digital.